(untitled) (Research, Society and Development, 2021)
Objective: To describe the findings reported in the scientific literature regarding joint changes in individuals affected by Chikungunya. Methodology: This study was carried out in the months of September to November 2020, using the databases: Pubmed, Scientific Eletronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (Lilacs), Science Direct and academic Google. There were no restrictions on language and year of publication. A search key associated with the Boolean connectors AND and OR was used: Chikungunya OR Chikungunya virus infection OR Infection, chinkugunya virus AND adult OR old man AND joint OR joint pains OR joint diseases OR alteration joint. All descriptors used in the search keys were obtained from the Medical Subject Headings (MeSH) database. The study excluded: literature review, book chapters, individuals under the age of 18 and studies carried out on animals. Results: Patients infected with Chikungunya may present, as symptoms, joint changes such as: chronic inflammatory polyarthritis, chronic post-chikungunya arthritis, inflammatory rheumatism, chronic joint pain associated with synovitis. The regions most reported for joint changes are the knee, wrist and ankle. joint pain can vary in duration. Most patients recover completely, but in some cases, joint pain can persist for months or years. Conclusion: Patients infected with Chikungunya may present joint changes in addition to the pain process. Further studies in this area are suggested in order to learn more about this inflammatory process that occurs in the joints of patients infected with this arbovirus.